Towards a human self-regulation system: Common and distinct neural signatures of emotional and behavioural control. (July 2018) - Langner, Robert; Leiberg, Susanne; Hoffstaedter, Felix; Eickhoff, Simon B.
Highlights: Earlier studies suggest a common brain network for controlling emotion and action. Two large-scale meta-analyses reveal disparate brain networks with limited overlap. Domain-general self-control is subserved by parieto-frontomedial-insular core network. Connectivity-based clustering and functional decoding support interdomain differences. Abstract: Self-regulation refers to controlling our emotions and actions in the pursuit of higher-order goals. Although research suggests commonalities in the cognitive control of emotion and action, evidence for a shared neural substrate is scant and largely circumstantial. Here we report on two large-scale meta-analyses of human neuroimaging studies on emotion or action control, yielding two fronto-parieto-insular networks. The networks' overlap, however, was restricted to four brain regions: posteromedial prefrontal cortex, bilateral anterior insula, and right temporo-parietal junction. Conversely, meta-analytic contrasts revealed major between-network differences, which were independently corroborated by clustering domain-specific regions based on their intrinsic functional connectivity, as well as by functionally characterizing network sub-clusters using the BrainMap database for quantitative forward and reverse inference. Collectively, our analyses identified a core system for implementing self-control across emotion and action, beyond which, however, either regulation facet appears to rely on broadly similar yet distinct subnetworks. These insights into the neurocircuitry subserving affective and executive facets of self-control suggest both processing commonalities and differences between the two aspects of human self-regulation.